Effet Du Stress Salin Sur Le Comportement Biochimique Et Anatomique Chez Deux Variétés De Piment (Capsicum Annuum L.) À Mila /Algérie - Karima Bouassaba; Saiida Chougui (European Scientific Journal, ESJ, 2018)
Soil salinity is a permanent threat to the survival of plants. The choice of a salt tolerant species could be a solution to this constraint. This paper focuses on the concept of adaptation and sensitivity during the vegetative phase of sweet pepper (Capsicum annuum L.) variety: Super marconi (Sp) and Marconi (M). Plants were stressed with different concentrations of NaCl ranging from 0, 25, 50 to 150 mM/l NaCl for 60 days. The results obtained showed that the application of stress results in a moderate decrease in plant size and the content of Chlorophyll a, b which declined during times of stress. An increase in proline content and soluble sugars was recorded in the leaves. It could be an indicator of salinity tolerance which explains the maintenance of a good water status among the studied plants. Regarding the ionic content (K+ and Na + ), salt stress caused a significant decrease in the content of K + , and a significant increase in Na+ content in both pepper varieties. Concerning anatomical structure of stems, the action of combined salts (50-150Mmol/L) causes a decrease in the size of the parenchymal cells, as well as the diameter of xylem vessels. It is concluded that the variety Super Marconi (Sp) is more tolerant to salinity compared to the variety Marconi (M). Hence, they have a significant role to play in agriculture, food, and economy.